Design and analysis of pseudo hadamard transformation and non-chaotic substitution based image encryption scheme - Prajwalasimha S N; Kavya S R; Tanaaz Zeba Ahmed (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In this paper, Pseudo Hadamard Transformation (PHT) and non-chaotic substitution based image encryption scheme has been proposed. Images are characterized by intrinsic properties such as, strong redundancy and correlation between the adjacent pixels, hence more vulnerable to cyber-attacks. In the proposed technique, the redundancy and correlation have been effectively reduced by pixel position transformation using PHT and pixel value variation using non chaotic substitution, providing two stage security in encryption for images. Fifteen standard test images are considered for experimental analysis. Better average Number of Pixel Changing Rate (NPCR) and Unified Average pixel Changing Intensity (UACI) are obtained for a set of standard test images compared to more popular existing algorithms.